The Impact of Boron Hybridisation on Photocatalytic Processes. (10th August 2022) - Marotta, Alessandro; Adams, Callum E.; Molloy, John J.
Abstract: Recently the fruitful merger of organoboron chemistry and photocatalysis has come to the forefront of organic synthesis, resulting in the development of new technologies to access complex (non)borylated frameworks. Central to the success of this combination is control of boron hybridisation. Contingent on the photoactivation mode, boron as its neutral planar form or tetrahedral boronate can be used to regulate reactivity. This Minireview highlights the current state of the art in photocatalytic processes utilising organoboron compounds, paying particular attention to the role of boron hybridisation for the target transformation. Abstract : The fruitful merger of organoboron chemistry and photocatalysis has led to the development of new technologies to access complex (non)borylated frameworks. Central to the success is control of boron hybridisation. This Minireview highlights the current state of the art in photocatalytic processes utilising organoboron compounds, paying particular attention to the role of boron hybridisation for the target transformation.